Rare Case of Double-Positive CD4/CD8 Immunophenotype in Lennert Lymphoma With Cutaneous Involvement: A Case Report. (23rd February 2022) - Kim, Joong Ho; Lee, Soo Kyung; Kim, Ho Young; Uh, Ji An; Lee, Jae Ho; Kim, Myoung Shin; Lee, Un Ha
Abstract: Lennert lymphoma is a lymphoepithelioid variant of peripheral T-cell lymphoma (not otherwise specified) with characteristics that do not fit into other peripheral T-cell lymphoma categories. Lennert lymphoma is primarily a nodal disease, and skin involvement may be exhibited. Cutaneous manifestations in Lennert lymphoma are nonspecific and include erythematous papules, nodules, and small plaques. Histological examination of cutaneous involvement characteristically presents epithelioid histiocytes and atypical small lymphocytes around vessels or appendages. A lymph node (LN) biopsy is essential for Lennert lymphoma diagnosis. In Lennert lymphoma, immunohistochemistry of both LNs and the involved skin reveals T-cell marker positivity. Although most Lennert lymphoma cases present with a single-positive CD4/CD8 immunophenotype, few cases present with a double-positive CD4/CD8 immunophenotype. We report a case of a 54-year-old woman presenting with fever, chills, general weakness, and a skin rash of erythematous patches on the trunk, extremities, and buttocks. A skin biopsy of the buttocks revealed atypical lymphocytes around the dermal vessels. In immunohistochemistry, these atypical lymphocytes stained positive for CD3, CD4, CD8, and CD68 but negative for CD20, CD30, and granzyme B. Similarly, a biopsy of the axillary LN revealed numerous epithelioid cells with atypical lymphocytes, exhibiting positivity for CD3, CD4, CD8, and CD68 but negativity for CD20, CD30, and S-100. Ki-67 was overexpressed in both the skin and LN. The final diagnosis of the patient was Lennert lymphoma with cutaneous involvement and a rare double-positive CD4/CD8 immunophenotype. The patient was transferred to another hospital for chemotherapy as per her request.